PENGARUH KONTRIBUSI SEKTOR PARIWISATA, INVESTASI TERHADAP PAD DAN PERTUMBUHAN EKONOMI DI KABUPATEN BADUNG - Rosidi, Eka Amelia; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 1 (2023): Vol.12.1. JANUARI 2023[1-85]DO - 10.24843/EEP.2023.v12.i01.p01, 2023)
This study aims to analyze the influence of the contribution of the tourism sector and investment on economic growth with local revenue (PAD) as the interventing variable. This research was conducted in Badung Regency during the period 2013-2020. This data is secondary time series data with seven years of observational data using participant observation data collection method. The data were analyzed using the SEM-PLS technique. The results this study indicate that the contribution of the tourism sector has a positive effect on economic growth. Investment has a positive effect on economic growth. The contribution of the tourism sector has a positive effect on PAD. Investment has positive effect on PAD. PAD has positive effect on economic growth. PAD is able to intervening variable of the contribution of the tourism sector to economic growth. PAD is not able to be an interventing variable of the effect of investment on economic growth. Keywords: Tourism Sector Contribution, Investation, Economic growth, Regional Original Income (PAD).